Toll-Like Receptors Expression and Signaling in Glia Cells in Neuro-Amyloidogenic Diseases: Towards Future Therapeutic Application - Dorit Trudler; Dorit Farfara; Dan Frenkel (Mediators of Inflammation)
Toll-like receptors (TLRs) are known to be expressed by innate immune response cells and to play a critical role in their activation against foreign pathogens. It was recently suggested that TLRs have an important role in the crosstalk between neurons and glial cells in the central nervous system (CNS). TLR signaling was reported to be associated with a yin-yang effect in the CNS. While TLR signaling was linked to neurogenesis, it was also found to be involved in the pathogenesis of neurodegenerative diseases. This paper will focus on TLR signaling in glial cells in neurodegenerative diseases such as Alzheimer's disease, prion diseases, amyotrophic lateral sclerosis, and Parkinson's disease. Understanding the pattern of TLR signaling in the glial cells may lead to the identification of new targets for therapeutic application.